SAT0018 Establishing the Content Validity of Omeract Preliminary Flare Questions (PFQ) for Detecting and Measuring Disease Exacerbations in Rheumatoid Arthritis. (23rd January 2014) - Bartlett, S. J.; Bingham, C. O.; Choy, E.; Xiong, J.; Boire, G.; Haraoui, B.; Pope, J. E.; Thorne, J. C.; Hitchon, C. A.; Tin, D.; Keystone, E. C.; Bykerk, V. P.
Abstract : Background: Flares in rheumatoid arthritis (RA) are common, poorly defined, and understudied in research and clinic settings. There is an urgent need for a validated tool that can reliably and comprehensively quantify RA disease exacerbations. The OMERACT RA Flare Group is an international collaboration of researchers and clinicians working together to develop an RA flare assessment measure. The rigorous, iterative process of qualitative and quantitative research with patients and health care providers that was used to identify the core set of domains to assess in RA flares was recently ratified by OMERACT attendees. Next, we developed a single item to assess each key domain (pain, function, fatigue, participation, coping and stiffness). Here, we report results of activities to establish the convergent validity of the OMERACT preliminary flare questions (PFQ). Objectives: To describe associations between responses to OMERACT PFQ items and similar questions from validated scales and indices commonly used in RA. Methods: 919 participants in the Canadian early ArThritis CoHort (CATCH) completed the OMERACT PFQs at routine clinic visits from 11-2011 through 1-2013. Participants rated their pain, function, fatigue, participation, coping and stiffness over the past week using an 11-point numerical rating scale. Measures of association (Pearson, Spearman, polychoric, polyserial) were calculated between PFQ responses and relevant items/indices from the HAQ, SF12, WPAI, RADAI and other commonly used measures. Results: 74% were female (74%), 83% White, and 54% completed at least high school. Mean (SD) age was 53.2 (14.7) years and RA duration of 5.9 (3.1) months. Across all, correlations were strongest between the PFQ pain rating and similar pain items from other scales (r's=.84 to .89). Moderate-strong correlations were evident among PFQ and other items querying function (r's= .66 to .76), fatigue (r's= .61 to .85), participation (r's=.64 to .78) and coping (r's=.48 to .58). Coping ratings were weakly to moderately related to depressed mood (r=.46), anxiety (r=.33), and stress (r=.10). PFQ stiffness ratings were moderately related to early morning stiffness (r=.61). Conclusions: In patients with early RA, there was substantial agreement between single item OMERACT PFQs for each domain and items from validated measures commonly used in RA research and care. These data provide evidence of convergent validity of PFQ items with other validated measures and add to the growing body of evidence supporting the validity of the OMERACT RA Flare Questionnaire. The OMERACT Flare Questionnaire is undergoing additional psychometric evaluation across a variety of RA populations and settings to establish its reliability, validity, and responsiveness prior to release for widespread use among clinicians and researchers. Disclosure of Interest: S. Bartlett: None Declared, C. Bingham III: None Declared, E. Choy: None Declared, J. Xiong: None Declared, G. Boire: None Declared, B. Haraoui: None Declared, J. Pope: None Declared, J. Thorne: None Declared, C. Hitchon: None Declared, D. Tin: None Declared, E. Keystone: None Declared, V. Bykerk Grant/research support from: The CATCH study was designed and implemented by the investigators and financially supported initially by Amgen Canada Inc. and Pfizer Canada Inc. via an unrestricted research grant since inception of CATCH. As of 2011, further support was provided by Hoffmann-La Roche Ltd., United Chemicals of Belgium (UCB) Canada Inc., Bristol-Myers Squibb Canada Co., Abbvie Inc, and Janssen Biotech Inc. (a wholly owned subsidiary of Johnson & Johnson Inc.)